2006
DOI: 10.1007/s10577-006-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genomic alterations on the transcriptome: a prostate cancer cell line case study

Abstract: Genetic instability may lead to the loss/gain of transcriptional control. Here we investigated the effect of genomic instability, that is loss/gain of chromosomal regions on the global transcriptome of prostate cancer cell line DU145. The genomic loss/gain map obtained through BAC array-based CGH was superimposed on the dynamic transcriptome of DU145 cells treated with serum for 0 h (serum starved), 2 h and 12 h. The genomic analysis suggested that in DU145 cells: (1) chromosomal gains are prominent than losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…It should be noted that Na V 1.1–1.3 and Na V 1.7 are located in chromosome 2q23‐24, whereas Na V 1.6 is located alone in chromosome 12q13; therefore, we speculate that chromosomal instability would influence the transcription profile in the CaC cells. This hypothesis is supported by a previous study, where it was shown that the chromosomal abnormalities in prostate cancer cell line DU145 impact the gene expression profile 29…”
Section: Discussionsupporting
confidence: 84%
“…It should be noted that Na V 1.1–1.3 and Na V 1.7 are located in chromosome 2q23‐24, whereas Na V 1.6 is located alone in chromosome 12q13; therefore, we speculate that chromosomal instability would influence the transcription profile in the CaC cells. This hypothesis is supported by a previous study, where it was shown that the chromosomal abnormalities in prostate cancer cell line DU145 impact the gene expression profile 29…”
Section: Discussionsupporting
confidence: 84%
“…The proliferation rate as reflected by rate of DNA synthesis was performed using 3 H thymidine incorporation assays as previously described . Cell cycle distribution was determined by staining DNA with propidium iodide (PI) (Calbiochem, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…aCGH analyses of human prostate cancer cell lines (11)(12)(13), xenografts (14,15), and prostate cancer tissues (16,17) have been reported. Although all of the above studies have used grossly dissected tissues, profiling of laser-captured, microdissected prostate cancer specimens has been shown to resolve cancerspecific genomic aberrations with higher sensitivity (17), Recently, Hughes et al (18) reported aCGH profiling of a small set of lasercaptured prostate cancer specimens.…”
Section: Introductionmentioning
confidence: 99%